The Seventeenth-Century Orange-Nassau Library : The Catalogue Compiled by Anthonie Smets in 1686, the 1749 Auction Catalogue and Other Contemporary Sources - Renting, A.D.; Renting-Kuijpers, J.T.C. (European History and Culture - Book Archive pre-2000., 1993)
Edited with introduction and notes. With notes on the manuscripts by A.S. Korteweg.